INCORPORATING RIGOR, REPRODUCIBILITY, AND TRANSPARENCY INTO AGING PROJECTS AND PAPERS. (11th November 2018) - Allison, D; W Brown, A
Abstract: Science remains our best means of obtaining objective knowledge of the world, and recent concerns regarding research rigor and reproducibility highlight areas in which we can do even better. This talk will introduce concepts of rigor, reproducibility, and transparency in science in general and related to aging research in particular. Specifically, I will discuss examples of historical and more recent errors in the literature and factors that contributed to the errors; methods of correcting errors and the challenges inherent in each; and some best practices and concepts for preventing errors in the first place. I will conclude by sharing concrete resources that are helpful in identifying, correcting, and preventing errors.